ANALISIS PENAMBAHAN RECLOSER DENGAN SKENARIO PECAH SECTION PADA PENYULANG NGULING ULP GRATI - SHOLICHAH, LAILATUS; Widihastuti, Ida (Elektrika, 2025)
The flow of electrical energy has the potential to experience disturbances which are often caused by short circuit currents between phases or phase to ground short circuits. Maintenance improvements by PT PLN (Persero) Grati Customer Service Unit (ULP) need to be carried out by adding tools to inhibit the blackout process. One of the largest distribution of electrical energy at ULP Grati is the Nguling Feeder, with 24 disruptions occurring in 2023-2024. This interference can be reduced by adding a recloser to the Nroll Feeder. Apart from making additions, it is necessary to carry out an analysis of the determination or placement of the recloser on the Nguling Feeder with the aim of detecting disturbance conditions. Several scenarios can be applied to obtain optimal results by taking into account the selling kWh value, SAIDI SAIFI, and the number of blackout areas as an effort to minimize blackout areas. The broken section method can be a fairly accurate calculation in determining the SAIFI SAIDI value and saved selling kWh. The results of the research show that the use of a recloser and determining its configuration is very important to minimize the outage area. Before installing the recloser, the SAIDI percentage was 43% with an index of 20.76, while the SAIFI percentage was 11% with an index of 5.50. After installing the recloser based on the section rupture scenario, the SAIDI SAIFI percentage decreased, namely: SAIDI 36% with an index of 17.24 and SAIFI 10% with an index of 4.97. This shows that the SAIDI SAIFI target as an indicator for measuring the recloser on the Nguling Feeder is appropriate for determining system reliability. Keywords: Broken Section, Recloser, Penyulang Nguling, SAIDI SAIFI ABSTRAKAliran energi listrik memiliki potensi mengalami gangguan yang sering ditimbulkan oleh arus hubung singkat antar fase atau hubung singkat fase ke tanah. Adanya perbaikan pemeliharaan oleh PT PLN (Persero) Unit Layanan Pelanggan (ULP) Grati perlu dilakukan dengan menambah alat untuk menghambat proses pemadaman. Distribusi energi listrik terbesar pada ULP Grati salah satunya adalah Penyulang Nguling, dengan 24 kali terjadi gangguan pada tahun 2023-2024. Gangguan tersebut dapat dikurangi denngan menambahkan recloser pada Penyulang Nguling. Selain melakukan penambahan, perlu dilakukan analisis penentuan atau peletakan recloser pada Penyulang Nguling dengan tujuan mendeteksi kondisi gangguan. Beberapa skenario dapat diterapkan untuk mendapatkan hasil optimal dengan memperhatikan nilai kWh jual, SAIDI SAIFI, dan jumlah section area padam sebagai updaya meminimalkan area padam. Metode pecah section dapat menjadi salah satu perhitungan yang cukup akurat dalam menentukan nilai SAIDI SAIFI dan kWh jual yang terselamatkan. Hasil dari penelitian menunjukkan bahwasannya penggunaan recloser dan penentuan konfigurasi memang sangat penting untuk meminimalkan area padam. Sebelum pemasangan recloser, persentase SAIDI adalah 43% dengan indeks 20.76, sedangkan persentase SAIFI adalah 11% dengan indeks 5.50. setelah dilakukan pemasangan recloser berdasarkan scenario pecah section, persentase SAIDI SAIFI mengalami penurunan, yakni: SAIDI 36% dengan indeks 17.24 dan SAIFI 10% dengan indeks 4.97. Hal tersebut menunjukkan bahwa target SAIDI SAIFI sebagai indikator pengukuran recloser pada Penyulang Nguling menjadi tepat guna untuk menentukan keandalan sistem.